2021
DOI: 10.1016/j.tele.2020.101516
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Addiction and Empathy: Moderating impact of personality traits among high school students

Abstract: Telematics and Informatics (2020). In press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 123 publications
0
27
0
Order By: Relevance
“…Conscientiousness plays a major role in this matter (Whaite et al, 2018). Personality traits can also affect one's addiction and empathy towards social media even from a young age (Dalvi-Esfahani et al, 2021). Moreover, even though people might share the same personality traits, another vital factor that influences the use of social media is an individual's purpose of using such platforms, as people use social media for different reasons and goals (Hughes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conscientiousness plays a major role in this matter (Whaite et al, 2018). Personality traits can also affect one's addiction and empathy towards social media even from a young age (Dalvi-Esfahani et al, 2021). Moreover, even though people might share the same personality traits, another vital factor that influences the use of social media is an individual's purpose of using such platforms, as people use social media for different reasons and goals (Hughes et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another important result of the study is the finding that prosocial behaviors reduce social media addiction in high school students (H 2 ). Some studies showed that there were short comings in social skills associated with social interactions and internet and social media addiction (Chua et al, 2020 ; Dalvi-Esfahani et al, 2021 ). While the effective use of the internet creates an opportunity for the adolescent, its excessive use may negatively affect the adolescent's physical, psychological, social and cognitive development (Hou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, earlier studies (e.g. [4,11,16,18,24,25]) demonstrate that there is a strong correlation between user personalities and their online behavior on social media. Some examples of applications that can take advantage from the user personality information include recruitment systems, personal counseling systems, online marketing, personal recommendation systems, and bank credit scoring systems to name a few [5,12].…”
Section: Introductionmentioning
confidence: 99%